Effect of lambing season on the productivity of ewes of the Karagouniko breed. - DELIGIANNIS (Κ. ΔΕΛΗΓΙΑΝΝΗΣ) K.; LAINAS (Θ. ΛΑΪΝΑΣ) Th. (Journal of the Hellenic Veterinary Medical Society, 2018)
Karagouniko breed and of known production history, kept under semi-intensive system, were used to study the effect of lambing season on their productivity. The ewes were divided into three groups according to lambing season: Group A (n = 56) with ewes lambed in late October, Group Β (n = 50) with ewes lambed in late November and Group C (n = 60) with ewes lambed in late December. Changes of body reserves of the ewes during lactation were normal with the ewes which suckled twins showing the greatest change in early lactation (P< 0.001). During the milking period the greatest change was found in the ewes that lambed late and, particularly, in those which suckled twins (P<0.05 - Ρ < 0.001). Early lambed ewes which suckled twins had significant longer lactation period and milk production than the late lambed ewes which suckled single lambs (P<0.05 - P<0.001). Birth weight of lambs was not affected by season of lambing; it was only affected by sex, with male Iambs being heavier than female lambs (P<0.001). However, growth of lambs during the suckling period was significantly affected by season of lambing with the early born single male lambs being heavier than those born late (P< 0.001). It is concluded that lambing season significantly affects the productivity of the ewes.